Financial Stability in the Basic Material Sector: The Roles of Capital Structure and Gender Diversity - Arsa Patmah; Tetiana Anatoliivna Bincharovska; Valerie Shanty (Yayasan Az Zukhruf Cendikia, 2026)
Purpose – This study aims to examine the effect of capital structure, inventory turnover, capital intensity, and gender diversity on financial distress. Design/methodology/approach – This study employs a quantitative approach using secondary data obtained from the annual financial statements of basic materials sector companies listed on the Indonesia Stock Exchange (IDX). The sample is selected using purposive sampling, and the data are analyzed using multiple linear regression with E-Views software. Financial distress is measured using the Altman Z-Score model, while the independent variables are measured using relevant financial ratios and gender diversity indicators. Findings – Findings – The results show that capital structure have a significant effect on financial distress. In addition, inventory turnover, capital intensity and gender diversity do not have a statistically significant effect on financial distress in basic materials sector companies during the study period Research limitations/implications – This study is limited to basic materials sector companies and the 2021–2024 observation period. Nevertheless, the findings provide insights for corporate management and investors regarding the importance of financial structure and operational efficiency in managing financial distress risk in capital-intensive industries. JEL : G33, G32, J16